(untitled) (Academia Science Repository, 2023)
This article provides detailed information about the life and creative work of artists such as Rasulkori Mamadaliev, Akbarkori Khaydarov, Mamurjon Uzokov, Jorakhan Sultanov, who are representatives of the traditional singing art of the Ferghana Valley.